EFFECT OF IBUPROFEN ALONE AND INCONJUGATION WITH VITAMIN E AND SELENIUM ON EXPERIMENTALLY INDUCED COCCIDIOSIS IN BROLIERS - Hafeez. M.A; A. Sattar; K. Ashraf; M. Mehdi; A. Rafique; M.S. Mahmood; F. Aslam; I. Hussain; M.R. Zia (Journal of Animal and Plant Sciences, 2020)
The aim of study was to determine the effect of (BrufenTM) alone and in conjugation with vitamin E and Selenium in broilers against coccidiosis. One hundred randomly allocated (25 birds in each group i.e., A, B, C & D) day-old broiler chicks underwent the current trial. Group A, B and C were challenged with 60,000-70,000 sporulated oocysts of genus Eimeria at 21st day of age. Group A and B were administered with (BrufenTM) and combination of (BrufenTM) with vitamin E and Selenium (E-SelTM) @ 100mg/kg body weight and 1ml/10 liters of drinking water, respectively. Group C and D were kept as negative (infected & un-medicated) and positive (un-infected & un-medicated) controls, respectively. Therapeutic response was measured on the basis of mortality, oocysts count, weight gains, coccidial lesion scorings and weight of lymphoid organs. Maximum mortality was observed in group C (17/25), followed by group A (12/25), than in group B (8/25) post coccidial infection. Coccidial lesion scores and oocysts count were significantly lower in groups (A & B) administered with Ibuprofen. Moreover, maximum weight gain and reduced lymphoid organ to body weight ratio were also observed in chicken of group B as compared to A, C and D. The study suggested synergistic and enhanced protective response of Ibuprofen in combination with vitamin E and Selenium against chicken coccidiosis.
Keywords: coccidiosis; ibuprofen; vitamin E and selenium; broilers